Analysis of molecular and (di)atomic dual-descriptor functions and matrices - Alcoba, Diego Ricardo (2017)
In this work, the dual-descriptor is studied in matrix form f(2) (r, r') and both coordinates condensed to atoms, resulting in atomic and diatomic (or where applicable, bond) condensed single values. This double partitioning method of the dual-descriptor matrix is proposed within the Hirshfeld-I atoms-in-molecule framework although it is easily extended to other atoms-in-molecules methods. Diagonalizing the resulting atomic and bond dual-descriptor matrices gives eigenvalues and eigenvectors describing the reactivity of atoms and bonds. The dual-descriptor function is the diagonal element of the underlying matrix. The extra information contained in the atom and bond resolution is highlighted and the effect of choosing either the fragment of molecular response or response of molecular fragment approach is quantified.